ENDOMETRIOSIS AND ITS CONSEQUENCES ON FERTILITY AND QUALITY OF LIFE – A HOSPITAL-BASED CROSS-SECTIONAL STUDY AT PMCH NAWABSHAH.: JPUMHS;2024:14:04,132-138. http://doi.org/10.46536/jpumhs/2024/14.04.570 . - Kainat1, Nusrat Fozia Pathan2, Bushra Noor Khuhro3, Shahzadi Pir4 , Rashida Akbar Ghumro 5, Resham Baloch6, Aqsa7. (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
BACKGROUND: Endometriosis is a disabling gynecological disorder that affects about 10% of reproductive-aged women globally, with far-reaching effects on fertility and quality of life QoL. Although the condition is worldwide in its prevalence, information from low resource settings such as Pakistan is limited. METHODS: Hospital-based cross-sectional survey of 360 women aged between 18–45 years having clinically or laparoscopically diagnosed endometriosis. Structured questionnaires for collection of data regarding demographic parameters, fertility background, severity of pain visual analog scale, VAS, and QoL Endometriosis Health Profile-30, EHP-30. Severity of the disease as per revised American Society for Reproductive Medicine ASRM criteria was categorized. Analysis of data performed by using SPSS version 26, wherein p<0.05 were considered significant. RESULTS: Participants’ mean age was 29.4 ± 6.2 years, and 62.5% had reported infertility 65.8% primary, 34.2% secondary. Severe pelvic pain VAS ≥7 was found in 58.3% of the participants, which was associated with advanced ASRM stages III/IV. QoL scores reflected significant impairment in pain 68.2 ± 12.4, emotional well-being 54.7 ± 15.2, and social functioning 49.3 ± 14.8. Advanced endometriosis ASRM III/IV was highly linked with infertility OR = 4.2, 95% CI: 2.8–6.3, p<0.001, and decreased socioeconomic status was associated with delayed diagnosis OR = 2.1, 95% CI: 1.4–3.2, p=0.008. CONCLUSION: Endometriosis has a major impact on fertility and QoL in women of Nawabshah, with diagnostic delays compounding disease burden. The implications of our findings underscore the need for enhanced diagnostic protocols, multidisciplinary management, and patient education in low-resource environments to forestall long-term sequelae.